Transient liquid phase bonding of γ′- precipitation strengthened Ni based superalloys for repairing gas turbine components. (January 2017) - Kim, Jeong Kil; Park, Hae Ji; Shim, Deog Nam; Kim, Dong Jin
Abstract: γ′-Precipitation strengthened Ni based superalloys are extensively being accepted for gas turbine components, because these material have excellent mechanical properties, as well as corrosion and oxidation resistance at high temperatures above 1000 °C. Transient liquid phase (TLP) bonding is an essential technique for gas turbine component repair. In this article, TLP bonding characteristics of two types of γ′ precipitation strengthened superalloys − GTD111 solidified directionally and Udimet520 wrought − were investigated to approve this technique for the repair of components. TLP bonding was carried out with an amorphous filler metal in various bonding conditions. The microstructural characterization of the joints was examined through optical microscopy (OM) and electron probe micro-analysis (EPMA). The experimental results showed clearly that TLP joints of these superalloys had different TLP bonding behaviors according to the bonding temperatures, and that microstructures such as dendritic structures and the melting points of the base metals had critical effects on these bonding behaviors.